Perforated Meckel's diverticulitis with small bowel obstruction and ischaemia - Lydia Pearson; Anantha Narayanan; Chris Kim; Paul Jackson (Elsevier, 2020)
Meckel's diverticulum (MD) is an uncommon congenital abnormality of the small bowel present in approximately 2% of the population. Common presentations due to MD in pediatrics include obstruction, gastrointestinal bleeding, and Meckel's diverticulitis. Clinical diagnosis is challenging in adults and pediatrics due to similarity to other more common causes of acute abdomen.A thirteen-year-old boy presented acutely with four days of central to right iliac fossa abdominal pain with associated vomiting. He had tenderness and peritonism in the right lower quadrant and raised inflammatory markers. He had a presumed diagnosis of perforated appendicitis and proceeded to operation. Intra-operative findings were of an inflamed appendix which was neither perforated nor necrotic. A perforated, gangrenous Meckel's diverticulitis with a mesodiverticular band causing internal herniation with a long loop of ischaemic small bowel was identified. This was reduced and the non-viable small bowel was resected. An ileostomy was formed with early reversal 12 days later. He made good clinical recovery.This case highlights the importance of reviewing the whole clinical picture when initial findings don't match expectations. We discuss diagnostic difficulty of complicated MD particularly within pediatrics, the importance of early assessment and surgical management, and demonstrate the potential significance of pathology associated.